(untitled) (Docentes 2.0 Journal, 2025)
In the knowledge era, driven by the digital revolution, digital skills are essential for individual and organizational success. The study aimed to analyze digital skills in the era of discernment from emerging approaches to artificial intelligence. The research was developed under the interpretive paradigm, systematic method, qualitative approach, and descriptive narrative design of bibliographic and cross-sectional documentary types. The universe consisted of scientific publications available in academic databases. One hundred seventy-five articles were selected using search formulas with descriptors such as “digital skills” AND “Artificial Intelligence (AI),” “knowledge era” AND “digital skills,” and “knowledge era” AND “Artificial Intelligence,” restricted to the period 2018-2023 and according to the defined inclusion and exclusion criteria. The methodology included the application of the PRISMA model for the selection of 20 relevant publications. The results showed that digital skills are key to optimizing artificial intelligence in education, benefiting students and educators. In conclusion, the need to ensure the effective and beneficial use of technologies in the educational field was highlighted.